Kajian Moralitas dalam Cerpen “Si Pemalu Menang Pemilu” Karya Dimas Jayadinekat dengan Pendekatan Objektif - Muhakim, Arief (sarasvati, 2025)
This research examines the morality aspect in the short story Si Pemalu Menang Pemilu by Dimas Jayadinekat with an objective approach. This short story tells the story of a young man named Yayat who unexpectedly becomes a candidate in the legislative elections. Starting from a shy but honest character, Yayat faces various moral dilemmas in a political world full of intrigue. The aim of this research is to identify the moral values contained in short stories and how these aspects are represented through the characters and storyline. The method used is objective analysis, which focuses on the structure of the text without considering external factors such as the author's background or social context. The research results show that this short story emphasizes the importance of honesty, responsibility and moral courage in facing challenges, especially in the political realm. The representation of morality in this short story provides insight into how individual integrity can be a determining factor in leadership.